Evaluasi Aksesibilitas Portal Akademik dan Pembelajaran Fakultas Ilmu Komputer Universitas Brawijaya berdasarkan Web Content Accessibility Guidelines (WCAG) - Mochammad Nurendra; Hanifah Muslimah Az-Zahra; Ismiarta Aknuranda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Information is basic need of every person for personal development and social environment and is an important part of national security. In addition, the right to obtain information is a human rights and the disclosure of public information is one of the important characteristics of a democratic country that upholds the sovereignty of the people. Several laws explicitly guarantee that information is available to everyone, including in rural and urban areas, and has equal access to that information regardless of physical perfection, so that persons with disabilities should be given equal opportunities. Websites have an important role, especially in nowadays information age. Websites becomes a platform for information providers to disseminate through online media. The education sector cannot be separated from the use of the website. Therefore, it is necessary to evaluate the accessibility of the website, where this research was carried out on the academic and learning portal website of FILKOM UB so that lecture activities at FILKOM UB can be more optimal. This study focuses on analysis related to website accessibility that follows the WCAG 2.0 standard using WAVE and Achecker evaluation tools. Based on the results, it was found that the academic and learning portal website of FILKOM UB did not fully meet the level A standard because there were problems related to link purpose and empty links which were found in almost all the features and pages evaluated. Referring to these results, it can be said that improvements are needed based on the Wave and Achecker documentation, especially in what to do and the relevance conformance level section..